2015
DOI: 10.1016/j.clinthera.2015.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Mirabegron, a β3-Adrenoceptor Agonist for Treatment of Overactive Bladder, in Healthy East Asian Subjects

Abstract: Our studies confirm the higher exposure levels of mirabegron in female compared with male East Asian subjects as found earlier in Western subjects. Furthermore, the effects of food on the pharmacokinetic profiles appeared to be similar among the 3 populations tested in our studies. The findings suggest that there are no significant pharmacokinetic differences among the Japanese, Taiwanese, and Chinese populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 20 publications
2
8
0
2
Order By: Relevance
“…The exposure of mirabegron was found to be lower under fed-conditions than fasted-conditions in Japanese and Taiwanese subjects. 37 Higher exposure levels of mirabegron were seen in female than male East Asian subjects, a trend that has previously been observed in Western subjects. 37 …”
Section: Mirabegronsupporting
confidence: 65%
See 1 more Smart Citation
“…The exposure of mirabegron was found to be lower under fed-conditions than fasted-conditions in Japanese and Taiwanese subjects. 37 Higher exposure levels of mirabegron were seen in female than male East Asian subjects, a trend that has previously been observed in Western subjects. 37 …”
Section: Mirabegronsupporting
confidence: 65%
“… 36 Further pharmacokinetic assessments and the impact of food on exposure of mirabegron have been conducted in healthy East Asian subjects. 37 No significant differences in pharmacokinetics were observed among Japanese, Taiwanese, and Chinese populations. The exposure of mirabegron was found to be lower under fed-conditions than fasted-conditions in Japanese and Taiwanese subjects.…”
Section: Mirabegronmentioning
confidence: 97%
“…Whether this novel property of mirabegron, that is, competitive antagonism of α 1A ‐ and α 1D ‐adrenoceptors, is relevant or not for its therapeutic efficacy obviously depends on the doses administered to the patient. Multiple 50 mg doses of mirabegron (approved dose level) to humans result in C max values from 20 to 60 ng·mL −1 , leading to plasma concentrations in the range of 60–150 nM, of which ≅70% is bound to plasma proteins (Iitsuka et al ., ), leaving a free plasma concentration of ≅20 to 50 nM. Pre‐clinical pharmacokinetic studies in rats after a single oral dose of 14 C‐mirabegron showed that the tissue : plasma radioactivity ratios are highest in the alimentary canal and excretory organs and that in some cases, upon repeated doses, the tissue : plasma ratios nearly reached 20‐fold (Department of Health and Human Services, U.S. Food and Drug Administration, ; Department of Health Therapeutic Goods Administration, Australian Public Assessment Report, ).…”
Section: Discussionmentioning
confidence: 99%
“…The model accounted for food intake (mirabegron bioavailability is greater under fasted conditions [23]) and also the 48% relative bioavailability of the oral suspension to the tablet previously demonstrated in adults (Astellas, data on file). The accumulation for a 24-h repeat dosing interval is w 2-fold higher than following a single dose [24], so the doses were multiplied by two to achieve steady-state exposures.…”
Section: Summary Tablementioning
confidence: 99%